Virtual multiple errands test (VMET): a virtual reality-based tool to detect early executive functions deficit in Parkinson’s disease - Cipresso, Pietro; Albani, Giovanni; Serino, Silvia; Pedroli, Elisa; Pallavicini, Federica; Mauro, Alessandro; Riva, Giuseppe (Frontiers in Behavioral Neuroscience, 2014)
Introduction: Several recent studies have pointed out that early impairment of executive functions in Parkinson’s Disease (PD) may be a crucial marker to detect patients at risk for developing dementia. The main objective of this study was to compare the performances of PD patients with mild cognitive impairment (PD-MCI) with PD patients with normal cognition (PD-NC) and a control group (CG) using a traditional assessment of executive functions and the Virtual Multiple Errands Test (VMET), a virtual reality-based tool. In order to understand which subcomponents of executive functions are early impaired, this experimental study aimed to investigate specifically which instrument best discriminates among these three groups. Materials and methods: The study included three groups of 15 individuals each (for a total of 45 participants): 15 PD patients with normal cognition (PD-NC); 15 PD patients with mild cognitive impairment (PD-MCI), and 15 cognitively healthy individuals (CG). To assess the global neuropsychological functioning and the executive functions, several tests (including the Mini Mental State Examination, Clock Drawing Test, and Tower of London test) were administered to the participants. The VMET was used for a more ecologically valid neuropsychological evaluation of executive functions. Results: Findings revealed significant differences in the VMET scores between the PD-NC patients versus the controls. In particular, patients made more errors in the tasks of the VMET, and showed a poorer ability to use effective strategies to complete the tasks. This VMET result seems to be more sensitive in the early detection of executive deficits because these two groups did not differ in the traditional assessment of executive functions (neuropsychological battery). Conclusion: This study offers initial evidence that a more ecologically valid evaluation of executive functions is more likely to lead to detection of subtle executive deficits.